An accelerated dose escalation with a grass pollen allergoid is safe and well‐tolerated: a randomized open label phase II trial. Issue 1 (2nd February 2016) - Chaker, A. M.; Al‐Kadah, B.; Luther, U.; Neumann, U.; Wagenmann, M.
Abstract: Background: The number of injections in the dose escalation of subcutaneous immunotherapy (SCIT) is small for some currently used hypoallergenic allergoids, but can still be inconvenient to patients and can impair compliance. The aim of this trial was to compare safety and tolerability of an accelerated to the conventional dose escalation scheme of a grass pollen allergoid. Methods: In an open label phase II trial, 122 patients were 1:1 randomized for SCIT using a grass pollen allergoid with an accelerated dose escalation comprising only 4 weekly injections (Group I) or a conventional dose escalation including 7 weekly injections (Group II). Safety determination included the occurrence of local and systemic adverse events. Tolerability was assessed by patients and physicians. Results: Treatment‐related adverse events were observed in 22 (36.1 %) patients in Group I and 15 (24.6 %) in Group II. Local reactions were reported by 18 patients in Group I and 11 in Group II. Five Grade 1 systemic reactions (WAO classification) were observed in Group I and 2 in Group II. Grade 2 reactions occurred 3 times in Group I and 2 times in Group II. Tolerability was rated as "good" or "very good" by 53 (86.9 %) patients in Group I and 59 (100 %) in Group II by investigators. Forty‐eight patients in Group I (80.0 %) and 54 in Group II (91.5 %) rated tolerability as "good" or "very good". Conclusions: The dose escalation of a grass pollen allergoid can be accelerated with safety and tolerability profiles comparable to the conventional dose escalation.